An analysis of archetypes in Batangas religious legends - Macatangay, Jose Clarete (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study analysed samples of folk narratives, specifically three Batangas religious legends, from the lens of Archetypal criticism. In a collective sense, analysing the archetypes of religious legends revealed Batangueños’ spirituality, religiosity, and traits as a people. The theme of faith as an archetypal subject relates to the Batangueños’ deep trust in God amidst difficult circumstances. The caregiver female character archetype recurs in the legends, while the ruler, everyman, rebel, and sage are the male archetypes revealed by the study. The characters’ negative traits as embodied in the shadow archetypes reflect that, true to their nature as human beings, Batangueños have human flaws. The water that represents the archetypal image symbolises the Batangueños’ life cycle of birth-death-resurrection, purification and redemption, fertility, and growth. As gleaned from the two legends, the situation archetype may be related to the Batangueños’ ownership of patron saints as part of their religiosity. Since the study focused on the non-etiological classification of legends, future researchers may study other legends that may reflect the peculiar culture of their localities.